ANALISIS SUMBER PENDAPATAN PENDIDIKAN DI SEKOLAH ISLAM VICTORIA, AUSTRALIA (2015–2023) - RAHARJO, NADA DIKURNIA; PUTRA, HELDY RAMADHAN; MUNADI, M.; SUHARDI, MUHAMAD (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2024)
This research analyzes income sources at Islamic Schools of Victoria from 2015 to 2023. The focus of the study includes income diversification, the contribution of each source to total income, and cross-year trends. This research method uses a library research approach, data analysis techniques with data reduction, data presentation and drawing conclusions. Data is processed from the school's annual financial report. The research results show that government grants dominate the source of income, with a contribution that continues to increase from 79.29% in 2015 to 84.73% in 2023. In contrast, the contribution to school fees shows a relative decline and total income shows an increasing trend despite fluctuations. Total revenue increased from 27 million in 2015 to 44.7 million in 2023, for an average annual increase of 5.7%. The small decline in 2020 can be attributed to the COVID-19 pandemic affecting tuition payments and donations. The main income therefore comes from government grants-operating, which contributed more than 80% of total income since 2020. Other sources, such as tuition fees, donations and investment income, show significant fluctuations. This study highlights the importance of strategic financial management for the sustainability of educational institutions. ABSTRAKPenelitian ini menganalisis sumber pendapatan di Sekolah Islam Victoria (Islamic Schools of Victoria) dari tahun 2015 hingga 2023. Fokus kajian mencakup diversifikasi pendapatan, kontribusi setiap sumber terhadap total pendapatan, dan tren lintas tahun. Metode Penelitian ini menggunakan pendekatan penelitian kepustakaan, teknik analisis data dengan reduksi data, penyajian data dan penarikan kesimpulan Data diolah dari laporan keuangan tahunan sekolah. Hasil penelitian menunjukkan Hibah pemerintah mendominasi sumber pendapatan, dengan kontribusi yang terus meningkat dari 79,29% pada 2015 menjadi 84,73% pada 2023. Sebaliknya, kontribusi biaya sekolah menunjukkan penurunan relatif dan Pendapatan total menunjukkan tren peningkatan meskipun terdapat fluktuasi. Total pendapatan meningkat dari 27 juta pada 2015 menjadi 44,7 juta pada 2023, dengan rata-rata kenaikan tahunan sebesar 5,7%. Penurunan kecil pada 2020 dapat dikaitkan dengan pandemi COVID-19 yang memengaruhi pembayaran biaya sekolah dan donasi. Oleh karena itu pendapatan utama berasal dari hibah pemerintah (government grants-operating), yang berkontribusi lebih dari 80% dari total pendapatan sejak 2020. Sumber lain, seperti biaya sekolah, donasi, dan pendapatan investasi, menunjukkan fluktuasi yang signifikan. Studi ini menyoroti pentingnya pengelolaan keuangan strategis untuk keberlanjutan institusi pendidikan.